2017
DOI: 10.1259/bjr.20160869
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral regions preserved by successful endovascular recanalization of acute M1 segment occlusions: a voxel based analysis

Abstract: Objective: To identify cerebral regions preserved by successful recanalization of the middle cerebral artery M1 segment and their association with early clinical outcome. Methods: 47 patients who underwent endovascular treatment for acute unilateral M1 segment occlusion were included. Successful recanalization was defined by a modified thrombolysis in cerebral infarction score of 2b/3. Final infarct volumes were segmented on follow-up MRI/ CT, 2-7 days post-symptom onset. The differences in topography of infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“… 26 , 27 Last and according to the different ischemic tolerance of gray and white matter, 28 30 both tissue types are likely to undergo infarction at different time points. As such, white matter tracts in an ASPECTS positive (gray matter largely infarcted) region may be salvaged by rapid reperfusion, 31 34 thus overestimating the infarct core and underestimating the potential beneficial effect of successful reperfusion in this area. 31 …”
Section: Discussionmentioning
confidence: 99%
“… 26 , 27 Last and according to the different ischemic tolerance of gray and white matter, 28 30 both tissue types are likely to undergo infarction at different time points. As such, white matter tracts in an ASPECTS positive (gray matter largely infarcted) region may be salvaged by rapid reperfusion, 31 34 thus overestimating the infarct core and underestimating the potential beneficial effect of successful reperfusion in this area. 31 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with previous studies that have evidenced that CST affection in chronic stroke stages correlates with more severe persistent deficits after spontaneous recovery 15,16 and worse outcome after MT. [27][28][29][30] However, there are only a few studies that have looked at the structural state of distinct key regions of the human motor network within the first hours after symptom onset and evaluated its association with functional outcome. Preinterventional magnetic resonance imaging-derived complete infarction of basal ganglia, 31 primary motor area, and bilateral centrum semiovale 32 was associated with worse NIHSS at discharge and poor mRS at follow-up, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A good CS supplies more blood flow to the ischemic penumbra but a poor CS will make ischemic penumbra more transformed into the core infarct area, and irreversibly damage the brain tissue [ 32 , 33 ]. Previous studies showed that a good CS reduce the core infarct volume, slow the growth rate of infarction and improve prognosis [ 34 , 35 ]. Stroke patients with LVO were difficult to benefit from MT.…”
Section: Discussionmentioning
confidence: 99%